Psychological flexibility in everyday life during post-surgical recovery in youths undergoing spinal fusion surgery and the association with parental responses—a prospective daily diary study using a single-case approach - Thorsell Cederberg, Jenny; Sundström, Felicia; Lavefjord, Amani; Bartels, Sara Laureen; Wicksell, Rikard K.; McCracken, Lance; Goubert, Liesbet (Frontiers in Psychology, 2025)
BackgroundChronic post-surgical pain (CPSP) affects ≈20% of children after major surgery, and the condition is associated with functional disability and ill-health. Psychological flexibility (PF) and parental factors have been shown to predict CPSP in youth following spinal fusion surgery. However, the daily dynamics of these processes throughout post-surgical recovery remain unknown. This study aimed at exploring how PF fluctuates in everyday life for youths undergoing spinal fusion surgery, and to investigate the associations between parental responses and adolescent PF.MethodsAdolescents with Idiopathic Scoliosis (AIS), aged 12–18 years, undergoing spinal fusion surgery at four hospitals in Belgium, and their parents, completed diaries, measuring adolescent PF and parental responses (including instructions to avoid or engage in activities, parental protective behavior, and parental pain catastrophizing) for 7 days, at five phases: before surgery (T0), at 3 (T1) and 6 weeks (T2), and 6 (T3) and 12 (T4) months, post-surgery. A single-case approach with aggregated results was used, including Tau-U calculations and cross-lagged correlations.ResultsIn total, data from 47 adolescents and seven parents were analyzed. Substantial within- and between-person variability characterized the patterns of adolescent PF. Cross-lagged correlations showed bidirectional relationships, demonstrating that parental responses predicted adolescent PF, and that adolescent PF, similarly, predicted parental responses.DiscussionThe results reveal the complex dynamics of PF among adolescents following surgery, and that parent-adolescent patterns after surgery may vary across both individuals and time. These findings also emphasize the need for idiographic pain research and individual-level assessments as well as person-centered treatments in clinical practice.